A new species of Xylochia from India - DURGA GUPTA, NITA MATHUR and O.P. SINGH, T. PRAMEELA DEVI*, P.N. CHOWDHRY, (Indian Phytopathology, 2007)
A new anamorphic fungus, Xylochia oryzae, isolated from the seeds of Oryza sativa is described, illustrated and compared with the type species of the genus Xylochia. This new species differs from the X. stegnosporioides, in conidiomatal hyphal cells and projections, conidiomatal morphology, conidial production, absence of longitudinal septa and presence of lipochroic oil globules in the conidia.